PENGARUH KEDUDUKAN, KREDIBILITAS, DAN REPUTASI MANTAN GUBERNUR RATU ATUT CHOISIYAH TERHADAP POLITIK KEBIJAKAN MELALUI GAYA KEPEMIMPINAN PEMERINTAHAN DI PROVINSI BANTEN - Ibnu Sofyan Ats-Tsauri Ibnu Sofyan Ats-Tsauri (Program Magister Ilmu Politik, Universitas Diponegoro, 2016)
Leadership is an activity to influence the behavior of others so that they can be directed to achieve specific goals. If someone has begun to influence the behavior of others, then began walking the leadership activities. In conjunction with the behavior of the leader (governor) Ratu Atut Chosiyah are usually done to his or society, that directs the behavior and conduct that support. Therefore, the function of leadership is to take decisions, therefore it can be seen if the leadership style practiced in terms of making decisions.The approach used in this study is a quantitative approach, and the type of research used in this study is a survey research. This survey method provides an overview of the variables at once examine the relationship between variables. Therefore the survey method will reveal the factual data based on the information obtained.Test instruments used are validity and reliability. Because the data in the form ordinal then transformed first into the interval. Then the data were analyzed using normality test, multicollinearity test, regression test, hypothesis testing (test f or simultaneous, coefficient determination test, test t / partial), correlation.Based on the results of the research, it is known that the influence of the position (X1) against the leadership style of the correlation coefficient of 20.3%. While the influence of credibility (X2) against the leadership style of the correlation coefficient of 40.9%. While the influence of reputation (X3) leadership style correlation coefficient of 49%, then it can be concluded that the independent variable on the dependent variable are positive and significant correlation. As for the coefficient of determination (R2) for the relationship of these variables has a value of 0.563 (56.3%), meaning that the dependent variable of leadership style can be explained by the independent variables (position, credibility and reputation) by 56.3%. While it's political policy can be explained by the independent variable by 53.5%.Keywords: Ratu Atut Chosiyah, Position, Credibility, Reputation, Policy, Leadership Styles